Analysis of Tool Wear and Surface Roughness in Turning ST41 by Insert Tool for Variation in Feed Rate - Manta, Faisal; Artika, Kurnia Dwi; Gunawan, Gad (Sebatik, 2025)
The turning process in manufacturing is used as the formation of cylindrical components, threads and drilling. ST41 steel has the ability to form, weld and treat, so it is used as a material for tools and automotive components. Insert tools with long life (live time), resistance to wear and high temperatures are better than conventional tools, making the type of insert tool used for various cutting processes. The quality of turning is determined by the selection of cutting parameters that are appropriate to the type of material being cut and the tool used. Lathe parameters are feed rate, cutting speed, deep cut. Feed rate parameters affect process time, surface roughness and tool wear. The use of excessive feed rate causes surface roughness outside tolerance and large tool wear. Therefore, research on ST 41 steel with insert tools to obtain optimal parameters is needed. Research using the experimental study method aims to analyze the effect of tool wear values ​​on changes in feed motion and surface roughness. Turning of ST41 steel on a GUT C0636D X 1000 lathe, CCMT 060204 insert tool, 0.6mm depth cut, 300 rpm cutting speed and feed rate variation of 0.1620, 0.3250, 0.8120 mm/rev. The results of the study measured the tool wear value increasing against feed rate and surface roughness. The highest tool wear value is 0.021 grams, namely with a feed rate variation of 0.8120 mm/rev, a surface roughness of 8.961 μm is obtained. The lowest tool wear value is 0.005 grams, namely with a feed rate of 0.6120 mm/rev, a surface roughness of 5.300 μm is obtained.